Effects of total Dose irradiation on Semiconductor devices - Haider F. Abdul Amir; Abdullah Chik; Chee, Fuei Pien (Universiti Malaysia Sabah, 2009)
The amount of ionizing radiation that semiconductor devices encounter during their lifecycle degrades both of their functional and electrical parameter performances. The different radiation environments either in space, high energy physics experiments, nuclear environment or fabrication process as well as for standard terrestrial operation possess an impact on the devices. This makes that the devices based on III-V semiconductors are probable to be critical components of future electronic systems as the demand for greater robustness and susceptibility to well function in rigorous radiation environments continue to increase. Expanding electronic systems into such radiation environments requires a full understanding of the effects that ionizing radiation will have on the semiconductor properties. In this research, analytical studies of the effects of ionizing radiation introduced in commercial-off-the shelf (COTS) NPN bipolar junction transistors (BITs) and optoelectronic devices by ionizing radiation, Cobalt- 60 (60Co) gamma (y) rays and x-rays had been performed. The Total Ionizing Dose (TID) effects are cumulative and gradually take place throughout the lifecycle of the devices exposed to radiation. Ionizing radiation causes ionization by possesses enough energy to break the atomic bonds which in turn create electrons and holes pairs in the devices. This phenomenon leads to ionizing damage as a result of trapping of excess charges on or near the surfaces of their insulating layers and interfaces. At the end of this testing, the devices under test (OUT) were found to undergo performance and also temporarily degradation in both of their functional and electrical parameters due to the accumulated total dose effects. These damaging effects were depending on their driving current and also the Total TID absorbed.